HUMAN LIFE OBLIGATIONS ACCORDING TO IMMANUEL KANT - Viktorahadi, R.F. Bhanu (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Immanuel Kant was a philosopher who put forward the idea of ​​rational ethical philosophy. He is also a philosopher who succeeded in interpreting ethics in terms of moral imperatives, not only in terms of efforts to achieve happiness. He also proposed a rational transcendental philosophy as opposed to a speculative metaphysical-dogmatic philosophy. The purpose of this research study is an attempt to study the inherent structure of the mind or the inherent laws of thought. In the context of rational transcendental philosophy, Kant directed his ethical or moral philosophy to religion, even though religion was not directly used as the basis for religion. The research method used in this research is Kant analyzing the nature of human knowledge, especially in his discussion of Transcendental Analytics. Kant applied the Analytical Method by asking three basic things. The result of this research is that Kant's life as a philosopher is divided into two periods. First, the precritical period was passed by adopting the rationalistic attitude launched by Leibniz and Wolff. Second, critical period. This second period was a time when Kant gradually abandoned rationalism because he was influenced by Hume. In this second period Kant began to change the face of philosophy radically. The research conclusion is that the highest goal of Kant's ethical philosophical thought is the social goal or essential social good (summum bonum).